Development of Interactive Food Web Learning Media to Improve Mastery of Science Concepts and Student Creativity - Lailatul Mukaromah; Joko Sutarto; Bambang Subali; Primus Devra Raihan (Jurnal Penelitian Pendidikan IPA, 2024)
The lack of use of technology-based learning media and low learning outcomes in mastery of science and science concepts and student creativity are problems at SD Negeri Kandangan 02 and Kandangan 04. The research aims to determine the feasibility and effectiveness of interactive learning media articulate storyline food web material to improve mastery of science and technology concepts and student creativity. The research method applied is the Define, Design, Development and Dissemination, development model with data collection techniques through observation, interviews, questionnaires, tests and documentation. The validation results for the media aspect 97.4%, material 97.6%, and language 98.2%, which stated that the media was very suitable for learning. Increasing mastery of science concepts in the experimental class obtained an average difference of 39.8 and an N-Gain of 0.76 with very effective criteria. Meanwhile, increasing mastery of science concepts in the control class received an average difference of 26 and an N-Gain of 0.52 with less effective criteria. Increasing student creativity in the experimental class obtained an average difference of 37.5 and an N-Gain of 0.59 with quite effective criteria. This research concludes that learning media is suitable and effective in increasing students' mastery of science concepts and creativity.